A novel method for enhancing nitrogen removal from wastewater treatment plant tailwater by zeolite-supported nano zero-valent iron substrate constructed wetland - Shuyu Luo; Jinhui Zhao; Shuai Zhang; Mingming Yang; Xingyu Fang; Boyan Xu; Jiabi Han (Desalination and Water Treatment)
The discharge of tailwater from wastewater treatment plants can cause pollution to receiving water bodies. Constructed wetlands (CWs) provide an economical approach to tailwater treatment. However, biological denitrification is limited due to the low bioavailability of carbon (C) relative to nitrogen (N) for denitrification in tailwater. Zeolite-supported nano zero-valent iron (Z-nZVI) and montmorillonite-supported nano zero-valent iron (Mt-nZVI) were prepared and used as substrates in CWs to evaluate their efficiency and mechanism of nitrogen removal from low C:N ratio tailwater. The results suggest that Z-nZVI can convert different forms of inorganic nitrogen to ammonium nitrogen (NH4+–N),which can be subsequently removed by the adsorption via zeolite or montmorillonite. The conversion rate for nitrate (NO3−–N) reached a maximum of 76.5%, electron transfer occurred during the reduction of NO3−–N by Z-nZVI. The removal rates of NO3−–N, NH4+–N, and total nitrogen by the Z-nZVI-substrate CW were 66.42 ± 1.33%, 86.56 ± 0.93%, and 69.92 ± 0.56%, which were, on average, 40.77%, 18.34%, and 35.73% higher than those observed in the CW with traditional gravel substrate. This presents a practical method for improving nitrogen reduction in CWs.